Dynamics of quality improvement programs – Optimal investment policies. (January 2016) - Duarte, Belmiro P.M.; Oliveira, Nuno M.C.; Santos, Lino O.
Highlights: A formulation for quality management programs for discrete time scenarios. A formulation for quality management programs for continuous scenarios. Explicit integration of the uncertainty in the formulations. The optimal improvement policies concentrate the efforts in the initial stages. Abstract: The problem of determining the optimal improvement programme quality effort in an organization over a given time horizon is posed as a dynamic optimization problem. The advantage of such approach with respect to a static scenario is discussed. The quality level is modeled as a function of the improvement investment, and of the costs of quality accounting for both prevention–appraisal and failure costs. The uncertainty on the quality level and failure cost variables is modeled by Itô processes. Two formulations of the dynamic quality improvement problem are described: one using a discrete time representation of the quality level dynamics and another using a continuous time representation. The application of these strategies is demonstrated by simulation of an illustrative example of a given organization. The optimal improvement policy results indicate the need to invest as soon as possible in order to reduce the failure cost, since it dominates the overall quality cost. Furthermore, the results are consistent with the fact that the improvement effort required is higher for firms with lower efficacy in converting that effort in terms of quality level.